2015
DOI: 10.4174/astr.2015.88.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term results of above-the-knee femoro-popliteal bypass with autogenous vein and polytetrafluoroethylene grafts

Abstract: PurposeTo analyze the long-term results of above-the-knee femoro-popliteal bypass (ATKFPB) with vein grafts compared with polytetrafluoroethylene (PTFE) grafts.MethodsA database of patients with chronic atherosclerotic occlusive disease who underwent ATKFPB was retrospectively reviewed. Characteristics of patient and arterial lesion, and follow-up results were compared between vein grafts and PTFE grafts. Graft patency was determined by periodic examinations of duplex ultrasonography or CT angiograms. Graft pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For study design, we focused on large single-and multicenter, prospective randomized studies that have been conducted in this regard since 1980 to allow discussion of our results with regard to the findings of these published studies [2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Supplementary Table, online only).…”
Section: Methodsmentioning
confidence: 99%
“…For study design, we focused on large single-and multicenter, prospective randomized studies that have been conducted in this regard since 1980 to allow discussion of our results with regard to the findings of these published studies [2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Supplementary Table, online only).…”
Section: Methodsmentioning
confidence: 99%
“…Higher patency rates of vein grafts have been noted previously. Heo et al 22 completed an analysis of 253 above-knee femoropopliteal bypass grafts and found that there were significantly higher primary assisted and secondary patency rates in the vein group at 10 years. They also showed that PTFE grafts have significantly higher rates of acute limb ischemia and a higher frequency of sudden occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that PTFE grafts have significantly higher rates of acute limb ischemia and a higher frequency of sudden occlusion. 22 On the other hand, vein graft occlusions tended to present as recurrent claudication, which may explain the higher rates of primary assisted patency and secondary patency. 22…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies have been conducted to determine risk factors of graft occlusion, which tested conduit materials, bypass procedures, indications for LEAB, coexisting disease, extent of the arterial lesion, presence of prior surgical or endovascular intervention, etc. [ 8 9 10 11 ]. Furthermore, we have known that the risk factors for limb loss are not only ischemic condition but also sites of the ischemic wound and presence of foot infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%